(untitled) (Purbanchal University Health Journal, 2024)
Introduction: Type II Diabetes Mellitus is a significant global health concern that has become prevalent worldwide, and its impact on morbidity and mortality is substantial. Metformin is a commonly prescribed medication for type II diabetes that interferes with the absorption of vitamin B12 in the gastrointestinal tract, which leads to neurological issues in patients. Objective: The aim of this study was to evaluate the vitamin B12 levels in Type II diabetic patients taking metformin at the Purbanchal University Teaching Hospital medical OPD. Method: A quantitative, descriptive cross-sectional study was done from May 2022 to April 2023 at the medical outpatient department of Purbanchal University Teaching Hospital, Gothgaun, Morang. Non-probability purposive sampling was done to select 385 Type II diabetic patients on metformin for 12 months. A structured questionnaire was used for data collection, which was validated with the consultation of experts. Result: It was found that the mean age (in years) with SD was 55.2±11.3; most of the respondents were female. The prevalence of low vitamin B12 was 21.8% among the study respondents. Diabetic patients on low vitamin B12 taking metformin were significantly associated with age over 50 years, a higher metformin dosage, a longer duration of use, and vegetarian dietary patterns. Conclusion: These findings emphasize the importance of regular monitoring of vitamin B12 levels in Type II diabetes mellitus and prolonged metformin treatment to prevent potential complications.